Ion-Specific Hydrogel Microcarriers with Biomimetic Niches for Bioartifical Liver System - Lin, Xiang (Wiley-VCH, 2025)
Bioartificial livers have showcased significant value in the treatment of acute liver failure (ALF). Current efforts are directed toward overcoming challenges in the development of microcarriers, with a specific emphasis on integrating higher-density liver cells to enhance detoxification capabilities. Here, inspired by the radial filtration model in hepatic lobules, ion-specific silk fibroin microcarriers are proposed with biomimetic niches for cultivating functional liver cells at high density. These biomimetic microcarriers are generated by capillary microfluidic device with controllable adjustments of ion type or concentration within the aqueous phase. When cultivating human induced pluripotent stem cell -differentiated mature liver cells on these recrystallized microcarriers, notably enhanced cell proliferation activity, as well as increased metabolic and secretory functionality is observed. Based on these features, the microcarrier-integrated bioreactor can effectively reduce hepatic transaminase levels and significantly improve urea, albumin production, and survival rate in rabbit ALF models is demonstrated. Thus, it is believed that the biomimetic microcarriers and their derived bioreactor may hold potential for clinical applications in managing ALF and other liver diseases.